FRI0167 Alopecia areata occuring during tnf blockers therapy : a french multicentric survey. (23rd January 2014) - Tauber, M.; Buche, S.; Berthelot, J.-M.; Aubin, F.; Cohen, J.-D.; Ghislain, P.-D.; Goujon, E.; Jullien, D.; Brixi, H.; Bardin, T.; Jeudy, G.; Guennoc, X.; et al.
Abstract : Background: Alopecia areata (AA) is an autoimmune disorder targeting the hair follicle, more frequently observed in patients with Pso, RA or IBD. While high amount of TNF is found in the hair follicle at the AA acute phase, TNF blockers have not demonstrated efficacy in its treatment. On the other hand, cases of AA occurring during TNF blockade have been reported. Objectives: To characterize the clinical features and the associated symptoms of AA occurring during TNF blockade and its outcome; to study the relationship between TNF blockade and occurrence of AA. Methods: From January 1 st 2011 to December 31 th 2012, French physicians prescribing TNF blockers (dermatologists, rheumatologists, gastroenterologists) were regularly asked, via their respective academic societies, to report all cases of AA appeared during anti-TNF therapy. Diagnosis of AA should be certified by a dermatologist. Results: Twenty-five patients were included (15 men, mean age: 39.4 years): 10 Pso (2 with associated PsA), 5 AS, 4 RA, 4 Crohn's diseases (1 associated with AS) and 2 ulcerative colitis. Eight patients (32%) had a personal or family autoimmune background (AA and/or vitiligo). Six patients (24%) had previously received biotherapy (anti-TNF or efalizumab) without developing AA, with a mean exposure duration of 5.8 months (mo). The TNF blocker prescribed at the time of AA onset was infliximab (INF) (n=9), adalimumab (ADA) (n=8) or etanercept (ETA) (n=8). The mean duration of exposure was 23.7 mo (1-89) (INF: 17.9; ADA: 16; ETA: 38 mo). The underlying inflammatory disorder was completely controlled in all patients, except 2. Clinical presentation of AA was mostly plaque-type of the scalp or the beard (n=21; 84%). Concomitantly, 7 patients (28%) developed vitiligo, psoriasiform eruptions or Hashimoto's thyroiditis. TNF blockers were stopped after AA onset in 11 cases and maintained in 14 cases. Among those who stopped the treatment, 3 (27%) had a worsening or stability of AA, whereas 8 patients (73%) had a partial or complete remission. Among those who maintained it, 4 (28%) had an unfavorable evolution while 9 patients improved (72%). One patient relapsed from AA after switching from ETA to ADA but healed again 2 weeks after stopping ADA. Mean follow-up duration was 27 mo. Conclusions: Occurrence of AA during TNF blockade may be considered as an incidentally autoimmune manifestation in patients with immune-mediated inflammatory disorders or as a new autoimmune-induced side effect of TNF blockers. This latter hypothesis is supported by the concurrent development of autoimmune symptoms in one quarter of our patients, a delay of onset after exposure to TNF blockers similar to the ones of other autoimmune-induced side effects and the relapse of AA after TNF blocker restart in one patient. Clinicians should be aware that AA might occur in patients receiving anti-TNF treatment. Withdrawal of treatment should not be systematic, especially if AA presentation is mild. Disclosure of Interest: None Declared